Heritage management in post-revolutionary Tunisia: a case study from Mhamdia - Turki, Sami Yassine; Stiti, Khaoula (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
Since the 2011 revolution, Tunisia has undergone a transformative phase characterized by emerging models of governance that prioritize grassroots initiatives and community participation in local affairs. Despite its manifold challenges, this political renewal has unfolded during political, socioeconomic, and security crises. Through a case study of the commune of Mhamdia, this article aims to examine two key aspects: (1) how communes can approach built heritage amidst the presence of national, international, governmental, non-governmental, profit, and non-profit actors, and (2) how heritage management can pose challenges, occasionally leading to the destruction of historical elements. This qualitative analysis, rooted in practitioner research, explores shifting paradigms and evolving dynamics within traditional and novel practices, shedding light on their impact on built heritage. The results demonstrate that, similar to national players, local elites also leverage built heritage to fortify their legitimacy, albeit through different means.